TEKNIK KAMERA SEBAGAI PENAMBAH UNSUR DRAMATIK DALAM PENYUTRADARAAN DRAMA TELEVISI “REKASA” - Bayangkara, Deila Shofi; Oktora, Dina Dwika (Offscreen, 2024)
The production of this work aims to create a comedy television drama by applying shot size, camera angle and camera movement camera techniques to add dramatic elements of conflict, suspense, Curiousity, and Surprise. the application of this technique is used to build an atmosphere in the story, so that the conveying of emotion and atmosphere in the story can be effective to the audience verbally and nonverbally.